2018
DOI: 10.1089/hum.2018.014
|View full text |Cite
|
Sign up to set email alerts
|

Results at 5 Years After Gene Therapy for RPE65-Deficient Retinal Dystrophy

Abstract: Previously, results at 2 years after subretinal injection of a recombinant adeno-associated virus vector expressing RPE65 (rAAV2-CB-hRPE65) in eight adults and four children with retinal degeneration caused by RPE65 mutations were reported. Now, results at 5 years after treatment in 11 of these subjects are reported. Subjects received a subretinal injection of rAAV2-CB-hRPE65 in the poorer-seeing eye, at either of two dose levels, and were followed for 5 years after treatment. The primary safety outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 36 publications
0
37
0
4
Order By: Relevance
“…Subgroup analyses were performed to compare BCVA at baseline of less than or more than 1.3 logMAR based on a recent study which reported that BCVA improvement was different between eyes with a baseline acuity at more than 1.3 logMAR (~20/400) vs. eyes with lower baseline BCVA [11]. Funnel plots were used to screen for potential publication bias.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Subgroup analyses were performed to compare BCVA at baseline of less than or more than 1.3 logMAR based on a recent study which reported that BCVA improvement was different between eyes with a baseline acuity at more than 1.3 logMAR (~20/400) vs. eyes with lower baseline BCVA [11]. Funnel plots were used to screen for potential publication bias.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Success in gene therapy for the autosomal recessive disease, specifically the RPE65 Leber Congenital Amaurosis clinical trials in the eye, has shown that gene therapy is an ideal treatment option for patients (Pennesi et al, ; Russell et al, ). However, the delivery of a healthy gene allele is not feasible to treat patients with the autosomal dominant disease.…”
Section: Discussionmentioning
confidence: 99%
“…Alignments were created by BLAST searches for CAPN5 in different species and then sequence alignments were performed using ClustalW (Thompson, Higgins, & Gibson, ). Sequence alignments were visualized using ESPript 3.0 (Robert & Gouet, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first successful in vivo gene therapy, in which the targeted cells are corrected genetically inside the body, was performed by AAV vectors encoding a functional RPE65 gene for a patient with retinal pigment epithelium deficiency. [ 2 ] In vivo gene therapy has also been accomplished for hemophilia‐B to restore the factor IX production by the liver. Another in vivo gene therapy has been carried out for CNS through peripheral vein infusion of AAV8 vectors containing an optimized codon for UGT1A1.…”
Section: Viral and Non‐viral Gene Therapymentioning
confidence: 99%